Does spatial perspective in virtual reality affect imitation accuracy in stroke patients? - Barhorst-Cates, Erica M.; Isaacs, Mitchell W.; Buxbaum, Laurel J.; Wong, Aaron L. (Frontiers in Virtual Reality, 2022)
Imitation is an important daily activity involved in social interactions, motor learning, and is commonly used for rehabilitation after stroke. Moreover, deficits in imitation of novel movements commonly occur after left hemisphere stroke (LCVA) in the syndrome of limb apraxia. In the current study, we used a novel virtual reality (VR) imitation paradigm to assess two factors that have remained underexplored in novel movement imitation: the imitation of complex, dynamic full-arm movements, and the effect of spatial perspective. VR holds promise as a tool for a number of clinical assessments and treatments, but has very rarely been studied in the context of imitation or diagnosis of apraxia. Thirty participants (18 with LCVA and 12 age- and education-matched controls) wore a VR headset and observed and imitated an instructor avatar demonstrating arm movements. Three spatial perspectives were examined within-subjects: first-person, third-person mirror, and third-person anatomical. Movements of the ipsilesional (left) arm were recorded and qualitatively coded for accuracy compared to the instructor avatar. Participants also completed embodiment questionnaires, a measure of limb apraxia (imitation of video-recorded meaningless movements), and three computerized background tasks that were hypothesized to evoke some of the same processing requirements of each of the three perspective conditions: a block-matching task, a block-mirroring task, and a mental rotation task. Imitation accuracy was highest in the first-person perspective, consistent with predictions, but did not differ between third-person mirror and anatomical. Surprisingly, patients and controls performed similarly on the imitation task for all spatial perspectives, with overall modest accuracy in both groups, and both patients and controls felt a moderate level of embodiment of their own avatar. Higher imitation accuracy related to quicker block-matching reaction times and higher mental rotation accuracy, regardless of perspective, but was unrelated to imitation of video-recorded meaningless movements. In sum, virtual reality provides advantages in terms of experimental manipulation and control but may present challenges in detecting clinical imitation deficits (limb apraxia).